Transglutaminase binding fusion protein linked to SLPI reduced corneal inflammation and neovascularization - Salica, Juan Pablo (2015)
Background: To study the effect of topical administration of a fusion protein (PF-MC) made up of N-terminal portion of the protease inhibitor Trappin-2 (which is a substrate of transglutaminasa-2) and SLPI (protein with anti-inflammatory, anti-bacterial and anti-viral ability), in an animal model of corneal inflammation and angiogenesis. Methods: An alkali injury was produced with a filter paper of 3 mm with 1 N NaOH during 40 seconds on the right cornea of 36 male Sprague Dawley rats, under general anesthesia. Animals were divided into three groups according to treatment. Group 1 was treated with 10 ul of PF-MC (200 ug/ml; n = 12), Group 2, with 10 ul of SLPI (200 ug/ml; n = 12) and Group 3 was treated with buffer (10 ul; n = 12) topically administered four times a day for up to 7 days. Half of the animals were sacrificed at day 3 before making a re-epithelialization time analysis with fluorescein staining at 18 and 24 hours. In the remaining animals corneal opacity was studied and digital photographs were taken at day 7 before doing euthanasia. Eyes were processed for histology and immunofluorescence. Results: Corneal ulcerated area was significantly lower in PF-MC treated animals compared to SLPI and buffer-treated animals at 18 hours and 24 hours postinjury. A clear cornea and fundus red reflex was only found among PF-MC treated animals. Histological analysis revealed a stratified corneal epithelium with at least three layers in all PF-MC animals at day 7. In this group there was a reduced number of PMNs in the corneal stroma at 3 and 7 days of follow-up. Besides, corneal neovascularization was much more extended in SLPI and Buffer animals than in animals treated with PF-MC. Conclusions: The binding of SLPI with Cementoin to transglutaminase seems to be an effective strategy to treat corneal inflammation and angiogenesis.